Correspondence on “How aromatic are molecular nanorings? The case of a six-porphyrin nanoring” - Deng, J-R; Bradley, D; Jirásek, M; Anderson, HL; Peeks, MD (Wiley, 2022)

(untitled)
A recent Research Article in this journal by Matito and co-workers claimed that none of the oxidation states of a butadiyne-linked six-porphyrin nanoring exhibit global aromaticity or antiaromaticity. Here we show that this conclusion is incorrect. Experimental data from NMR spectroscopy for a whole family of nanorings provide strong evidence for global ring currents. The NMR data reveal these ring currents directly, without needing analysis by density functional theory (DFT). Furthermore, DFT calculations reproduce the experimental results when a suitable functional is used.